Lupus-Like Syndrome Caused by 5-Aminosalicylic Acid in Patients with Inflammatory Bowel Disease. (1st May 1999) - Kirkpatrick, Andrew W; Bookman, Arthur A; Habal, Flavio
Abstract : BACKGROUND: Although 5-aminosalicylic acid (5-ASA) preparations used to treat inflammatory bowel disease are reported to have fewer side effects than sulphasalazine, increased clinical use of these compounds has resulted in increased reports of significant side effects. OBJECTIVE: To report four patients with antinuclear antibody-positive migratory arthralgias and acute inflammation unrelated to the underlying inflammatory bowel disease, fulfilling the criteria of a drug-induced lupus-like syndrome. SETTING: A university-affiliated teaching hospital. INTERVENTION: Cessation of treatment with 5-ASA compounds. RESULTS: The cases described constitute a drug-induced lupus-like syndrome. All patients improved rapidly after discontinuation of 5-ASA compounds. CONCLUSIONS: Reversible lupus-like syndrome appears to be a rare but significant side effect of 5-ASA compounds. Patients treated with 5-ASA compounds who experience acute inflammatory symptoms or clinical deterioration not related to their gastrointestinal disease should be screened to rule out a lupus-like reaction.